The Impact of Knowledge Management and Strategic Planning Towards Organizational Innovativeness and Organizational Competitiveness on Bed And Breakfast Industries in Kota Wisata Batu - Hananiel M. Gunawan; Priskilla Napitupulu; Yanuar Dananjaya (Dinasti International Journal of Education Management And Social Science, 2025)
The dynamic of competition forced companies to focus on strategies and analysis of the current environment. The focus can be done in the form of Knowledge Management and Strategic Planning. Knowledge management focuses how an organization manages the process of creating, store, access and also disseminate important information and resources throughout the organization. Strategic planning is the process of how companies and organizations analyze internal and external environment. This focus will enable companies to improve Organizational Innovativeness that later will improve Organizational Competitiveness. The object of this research is Bed and Breakfast Industry in Kota Wisata Batu. Tourism is a promising industry as more domestic and international tourists are coming and visiting popular tourist destinations in Indonesia. Kota Wisata Batu is chosen as it has developed as one of the main tourist destination in Indonesia. The sample used is 100 small to medium sized bed and breakfast business in Kota Wisata Batu. It is found that both Knowledge Management and Strategic Planning positively affect Organizational Innovativeness which in turn positively affect Organizational Competitiveness